Iapir quadridentatus sp. nov., a new torridincolid beetle from Brazil (Coleoptera: Myxophaga: Torridincolidae) - Pinto, Valeria Araújo Braule; Da Fonseca, Claudio Ruy Vasconcelos; Hamada, Neusa (Zootaxa, 2011)
The adults and larvae of a new species of Torridincolidae, Iapir quadridentatus sp. nov., are described from Pernambuco State, Brazil. This represents the first record of the family from Northeast Brazil. Larvae and adults were found on submerged leaves of Mourera sp. (Podostemaceae).